Beneško gledališče - Kravos, Bogomila (Jezik in slovstvo, 2016)
The article offers some initial thoughts about theatrical activities in the region of the Veneto valleys, i.e., the Alta Val Torre Valley, the Nadiža Valley and Resia, especially those activities that used to join these regions and that are in need of thorough examination. The archival materials should be supplemented by personal testimonies and detailed descriptions of how people received the most popular performances. A thorough analysis of the achievements and reception of the theatrical performances presents a unique opportunity to demonstrate how the peculiar dramatic expression of the troupe came about, and where the key actors found the inspiration to mix the bitter facts of existence with humour. The same analysis should examine how different ways of perception merge into a single theatrical expression that displays the spirit of the time and space. Such comprehensive research of each step in the history of the Veneto Theatre will reveal the axes around which its growth revolved and which connect the region of Veneto with the region of the Isonzo Valley.
Keywords: Beneško gledališče; Beneška Slovenija; Slavia Friulana; kulturno izročilo